By the Letter of Law? The Effects of Administrative Adjudication for Resolving Disputes in NYC's Restaurant Grading Initiative. Issue 8 (November 2021) - Silver, Diana; Rothbart, Michah W.; Bae, Jin Yung
Administrative adjudication can serve as a quasi-judicial forum for resolving disputes resulting from government regulations. New York City recently required restaurants to post letter grades reflecting their compliance with food safety regulations and incorporated an easily accessible administrative adjudication system into its policy design. This study examines the implementation of this feature of the policy by using a regression discontinuity framework to explore the effects of the grading policy on adjudication processes and regulatory outcomes. Quantitative data included 222, 527 food safety inspection records (2007–2014); qualitative data included interviews, observations, and document review. Restaurants were more likely to have violations reduced and grades improved at adjudication when grades were at stake. Moreover, adjudication outcomes were highly sensitive to score differences near grade cut-points. Professional representatives helped restaurants to negotiate the interpretation of rules in the quasi-judicial proceedings, softening rigidity of regulations. Representatives' expertise was consistent with being "repeat players, " which may distort the use of such forums to ensure justice and fairness. This study illuminates the ramifications of including alternative dispute resolution systems in the implementation of regulatory policies.